Power and Its Discontents: Anywaa's Reactions to the Expansion of the Ethiopian State, 1950-1991 - Feyissa, Dereje (The International journal of African historical studies, 2015)
Imperial rule under Haile Selassie and the contradictions it generated has received considerable scholarly attention, especially regarding the many local forms of protest that emerged against the Ethiopian state project.* 1 The Woyane revolt in the northern province of Tigray in 1943, rebellion in the southeastern province of Bale throughout the 1960s, and the peasant rebellion in the northwestern province of Gojam in 1967, are paradigmatic cases of "power and protest" in imperial Ethiopia. Popularized by the works of Gebru Tareke, these uprisings are typical of inconclusive agrarian revolts with inchoate local peasant consciousness, and in the Bale case, with a cross-border Somali dimension.2 This article draws upon previously neglected archival documents, found in the regional headquarters of Gambella,3 to tell of a rather different kind of revolt in which the resilience of local identities has been more important than the notion of incohate "class consciousness" suggested by Gebru.